2009
DOI: 10.1103/physrevb.79.094509
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling studies in a homogeneously disordereds-wave superconductor: NbN

Abstract: We report the evolution of superconducting properties as a function of disorder in homogeneously disordered epitaxial NbN thin films grown on (100) MgO substrates, studied through a combination of electrical transport, Hall Effect and tunneling measurements. The thickness of all our films are >50nm much larger than the coherence length ξ 0~5 nm. The effective disorder in different films encompasses a large range, with the Ioffe-Regel parameter varying in the range k F l~1. 38-8.77. Tunneling measurements on fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 32 publications
(20 reference statements)
13
46
1
Order By: Relevance
“…At higher disorder, one observes that the conductivity becomes a strongly increasing function of ω, which is a signature of incipient localization in a disordered metal [17][18][19]. Consistent with this, dc transport has shown that as T c is suppressed, the resistivity of all lower T c samples show a negative temperature coefficient at low T [16]. Localization modified Drude and Drude-Simith models have been proposed to include localization effects in such disordered systems and can reproduce the spectra with positive slope [18].…”
supporting
confidence: 58%
See 2 more Smart Citations
“…At higher disorder, one observes that the conductivity becomes a strongly increasing function of ω, which is a signature of incipient localization in a disordered metal [17][18][19]. Consistent with this, dc transport has shown that as T c is suppressed, the resistivity of all lower T c samples show a negative temperature coefficient at low T [16]. Localization modified Drude and Drude-Simith models have been proposed to include localization effects in such disordered systems and can reproduce the spectra with positive slope [18].…”
supporting
confidence: 58%
“…Details of fabrication and measurement can be found in Ref [16]. The spectra were fitted by using the theory of Larkin and Ovchinnikov and Feigelman and Skvortsov [27,29].…”
Section: Extraction Of Superconducting Gap ∆ and De-pairing Factormentioning
confidence: 99%
See 1 more Smart Citation
“…24 for the critical superconductive state (section 5.4). This is due to the averaging of the peak position eV = ∆ 0 + ∆ (j) P over a broad distribution P (∆ P ) of the local pairing gaps ∆ We emphasize again that the results obtained in this section give the averaged tunneling conductance which can be measured with a large-area junctions, such as the ones used in [41]. They may differ significantly from the local tunneling conductance measured by a small tip and discussed in the following subsection.…”
Section: Tunneling In a Superconductormentioning
confidence: 77%
“…Further investigations on the superconducting properties show that for low disorder NbN follows the conventional BCS behavior [11,12]. However, as we approach the SIT the superconducting state is characterized by a gradual loss in the coherence peak in the tunneling density of states and a linear variation of the superfluid density with temperature over a large temperature range.…”
Section: Figure 4 (A) Shows the ρ(Ht) As Function Of T For A Film Wimentioning
confidence: 79%